Log in to add a comment

Log in to add a comment

----------------------------------------------------------------------------------------------------------------------Remember , the text between the brackets is only given to explain it to you properly....you may not write them in your paper.

----------------------------------------------------------------------------------------------------------------------

Please mark it as the best

----------------------------------------------------------------------------------------------------------------------

= 2x =5-3

=2x = 2

x =2/2

x = 1.

By substituting the value of x in the above equation we get

2(1) + 3 =5.